1988
DOI: 10.1177/000331978803900210
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsied Case of Systemic Lupus Erythematosus with Pulmonary Hypertension—A Case Report

Abstract: The authors report an autopsied case of systemic lupus erythematosus (SLE) with pulmonary hypertension. The patient was a forty-five-year-old female who had been troubled by obstinate Raynaud's phenomenon for ten years before the definite diagnosis of pulmonary hypertension was made. Microscopic examination of the pulmonary vasculature yielded findings consistent with plexogenic pulmonary arteriopathy. However, the deposition of immune complexes in the pulmonary vascular endothelium was not detected by enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Low-grade lesions are characterized by "onionskin" thickening of arterioles and arteries, whereas high-grade lesions show vasoproliferative and dilatation lesions. In reported cases of PAH associated with SLE, only low-grade lesions vascular lesion have been described [1]. Our case presented with numerous high-grade pulmonary hypertensive lesions.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Low-grade lesions are characterized by "onionskin" thickening of arterioles and arteries, whereas high-grade lesions show vasoproliferative and dilatation lesions. In reported cases of PAH associated with SLE, only low-grade lesions vascular lesion have been described [1]. Our case presented with numerous high-grade pulmonary hypertensive lesions.…”
Section: Discussionmentioning
confidence: 62%
“…Clinical data suggests that a "pulmonary Raynaud's phenomenon" correlates with the development of PAH in SLE patients [1,5]. However, a recent study indicates that pulmonary hypertension develops in patients with SLE as result of abnormal inflammatory reaction which affects the blood vessels.…”
Section: Pulmonary Hypertension and Slementioning
confidence: 99%
See 1 more Smart Citation
“…38 Plexogenic arteriopathy as a cause of pulmonary hypertension in SLE was described by Roncoroni, et al in 1992, 39 and later reported in other isolated cases. [39][40][41][42] We cannot assure that it is a sign of PHT, as it may be due to recurrent pulmonary thromboembolism or the presence of capillaritis. However, the absence of any marker of those primary events is highly suggestive of lupus-related PHT.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, most patients with SLEand PHwere classified as idiopathic (5). In several autopsied cases, plexogenic pulmonary arteriopathy was revealed, which is characteristic of primary pulmonary hypertension (PPH) (6), and the idiopathic PH may be very similar to PPH. Although the differential diagnosis between chronic pulmonary thromboembolism (CPTE) and idiopathic pulmonary hypertension is sometimes difficult, the present case was diagnosed as having idiopathic pulmonary hypertension rather than CPTE, due to the lack of evidence of arterial stenosis/webs and localized areas of decreased attenuation and vascularity sharply marginated from adjacent areas on CT (7), and the lack of evidence of coagulation and fibrinolysis on laboratory data at anytime.…”
Section: Discussionmentioning
confidence: 99%